Peran Dukungan Sosial Terhadap Adaptabilitas Karier Mahasiswa : Studi Literatur Sistematis - Handayani, Izmi; Kurniawati, Farida (Universitas Pendidikan Mandalika, 2023)
This study aims to describe career adaptability and the role of social support as a predictor of career adaptability among higher education students. This research method used a Systematic Literature Review (SLR) by collecting articles that match the criteria from three databases (ProQuest, Sage, and Scopus) for the last 10 years (2013-2022). Eleven articles were then analyzed by using content analysis. The findings reported that two theories were used: Career Construction Theory (CCT) and Social Cognitive Career Theory (SCCT). Social support had a role in increasing higher education students’ career adaptability. Social support could be perceived by parents, teachers, friends, or significant others. Besides, it could also be seen from aspects such as emotional and objective support. Social support was proven to have a role in increasing higher education students’ career adaptability.